Advancement and applications of nanotechnology in breast surgery: a comprehensive literature review - Hakim, Tahmina; Tabassum, Azra; Lim, Caitlin (International Surgery Journal, 2025)
Breast cancer is the most common malignancy affecting women worldwide and remains a major cause of cancer-related mortality. Although conventional treatments such as surgery, chemotherapy, and radiotherapy are effective in early stages, their efficacy decreases in advanced and metastatic cases. Nanotechnology has emerged as a transformative approach in oncology, offering precise diagnosis, targeted therapy, and innovative surgical applications. This review synthesizes recent literature on nanotechnology-based strategies in breast cancer management, emphasizing diagnostic imaging, targeted drug delivery, surgical enhancement, and postoperative wound healing. Databases including PubMed, Scopus, and Google Scholar were searched for relevant studies published between 2015 and 2024, focusing on preclinical and clinical advancements. Nanomaterials such as liposomes, micelles, dendrimers, and metallic nanoparticles have shown significant promise in improving therapeutic efficacy through site-specific delivery and controlled drug release. Intraoperative imaging agents and nanoprobes facilitate accurate tumour margin identification and sentinel lymph node (SLN) mapping. Nanofibers and nanohydrogels enhance wound repair and reduce infection risk. Emerging theranostic and nanorobotic systems integrate diagnostic and therapeutic functions, improving surgical precision while minimizing tissue damage and systemic toxicity. Nanotechnology is reshaping the landscape of breast cancer surgery and treatment. Its integration into diagnostic and therapeutic protocols enhances precision, minimizes invasiveness, and optimizes patient outcomes. Despite promising preclinical evidence, clinical translation remains limited by challenges such as biocompatibility, immune clearance, and regulatory barriers. Continued interdisciplinary research is essential to advance nanotechnology toward safe, effective, and personalized breast cancer care.